The impact of lower sea-ice extent on Arctic greenhouse-gas exchange - Parmentier, Frans-Jan W.; Christensen, Torben R.; Sørensen, Lise Lotte; Rysgaard, Søren; McGuire, A. David; Miller, Paul A.; Walker, Donald A. (Nature climate change, 2013)
An increasingly ice-free Arctic Ocean could have significant implications for greenhouse-gas sources and sinks in the Northern high latitudes. In this Review, the impact of diminishing sea-ice extent on greenhouse-gas exchange in both marine and terrestrial Arctic environments is synthesised and discussed. In September 2012, Arctic sea-ice extent plummeted to a new record low: two times lower than the 1979–2000 average. Often, record lows in sea-ice cover are hailed as an example of climate change impacts in the Arctic. Less apparent, however, are the implications of reduced sea-ice cover in the Arctic Ocean for marine–atmosphere CO 2 exchange. Sea-ice decline has been connected to increasing air temperatures at high latitudes. Temperature is a key controlling factor in the terrestrial exchange of CO 2 and methane, and therefore the greenhouse-gas balance of the Arctic. Despite the large potential for feedbacks, many studies do not connect the diminishing sea-ice extent with changes in the interaction of the marine and terrestrial Arctic with the atmosphere. In this Review, we assess how current understanding of the Arctic Ocean and high-latitude ecosystems can be used to predict the impact of a lower sea-ice cover on Arctic greenhouse-gas exchange.